2010
DOI: 10.3354/aei00015
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preference of recaptured Atlantic salmon Salmo salar following simulated escape from fish pens during autumn

Abstract: Escapes of farmed fish from coastal farms around the world are believed to have genetic and ecological consequences for wild fish populations. Each year there are numerous escapes of adult farmed Atlantic salmon Salmo salar. However, survival until maturity appears to be low. One possible explanation is that many of these salmon have difficulties switching to live prey. To address this possibility, growth rate and dietary preference were recorded in recaptured salmon released in 3 groups from August to October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 36 publications
3
37
1
Order By: Relevance
“…The content of the TAG FA 18:2n-6 in farmed salmon is typically above 10%. In contrast, the level of 18:2n-6 was low (< 2.5%) in sea-ranched salmon in Iceland and in farmed salmon released as smolts and recaptured in Norway after 1 to 3 yr at sea (Olsen & Skilbrei 2010).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The content of the TAG FA 18:2n-6 in farmed salmon is typically above 10%. In contrast, the level of 18:2n-6 was low (< 2.5%) in sea-ranched salmon in Iceland and in farmed salmon released as smolts and recaptured in Norway after 1 to 3 yr at sea (Olsen & Skilbrei 2010).…”
Section: Introductionmentioning
confidence: 85%
“…Post-smolts that escape during their first summer in net pens in seawater may return to freshwater to spawn after 1 to 3 yr at sea (Skilbrei 2010a,b), with much higher long-term survival rates than adult escapees (Skilbrei et al 2015). Reports have showed that the stomachs of most escaped Atlantic salmon are empty (Hislop & Webb 1992, Soto et al 2001, Morton & Volpe 2002, Abrantes et al 2011) and 2 studies demonstrated that the FA profile in adult escapees was similar to those given fish feed (Olsen & Skilbrei 2010, Abrantes et al 2011. For these reasons, it has been suggested that fully grown salmon have a limited ability to switch to natural prey if released, that immature fish will suffer from high mortality, and that fish that have started the sexual maturation process at the time of escape will have a much higher chance of surviving until they can enter a river to spawn, normally in the same year that they escaped (Skilbrei et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish were then classified into either early escapees or newly escaped fish according to the content of the signature fatty acid 18:2(n-6). The level of this fatty acid is normally below 2.5% in sea-run and farmed salmon that has escaped early in life, and approximately 10 to 12% in fish feed and recently escaped farmed salmon (Jónsson et al 1997, Olsen & Skilbrei 2010. According to the method described by Skilbrei et al (2015b), the fish here were classified into 2 categories based on the level of the fatty acid 18:2(n-6): recently escaped (i.e.…”
Section: Fatty Acid Analysis and Classification According To Dietary mentioning
confidence: 99%
“…Past studies on escapee behaviour found that recapture fisheries are a realistic option for reducing the impact of escape events . However, fishing efforts need to be initiated immediately following the event and cover a large area, as salmon may either remain near the farm site (Olsen & Skilbrei 2010) or disperse rapidly following release (Skilbrei et al 2010). A study in southern Norway found that trawling for escapees was not very efficient, whereas gillnetting had greater success, especially when carried out over a large area for an extended period (Skilbrei & Jørgensen 2010).…”
Section: Introductionmentioning
confidence: 99%